Perceptions of care & patient-provider communication by varying identity groups in a collegiate health clinic - Yewande Addie; Tatiana Maser; Cecilia Luna; Casey Rayfield; Kelli Agrawal (The Beryl Institute, 2020)
LGBTQ patients experience discrimination and poor access to quality health care, but there is little inquiry on the experiences of LGBTQ patients in student health clinic. The purpose of this study was to examine the quality of patient-provider communication (PPC) among sexual and gender minority patients, especially those who have intersecting minority identities, in a student healthcare setting. An online survey measured PPC using the Communication Assessment Tool (CAT) and contextual questions regarding identity and perceptions of judgment. Analysis tested intersectional variance in both. A convenience and snowball sample of 102 respondents, 18+, that utilized health services at a public university in the southeastern United States were surveyed in the summer of 2019. Patients of Color (M = 8.16, SD = 5.69) perceived stronger PPC than Whites (M = 5.41, SD = 5.27), which deviates from much of the current literature available. Heterosexuals (M = 7.82, SD = 5.65) perceived stronger PPC than LGBQ (M = 4.56, SD = 4.98) patients, which aligns with most current literature. Additional research is recommended for generalizability among student health populations in other university campuses and preliminary findings indicate a need to improve PPC between clinicians and sexual minority patients in student health settings. Experience Framework This article is associated with the Policy & Measurement lens of The Beryl Institute Experience Framework. (http://bit.ly/ExperienceFramework) <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Policy%20%26%20Measurement%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens.